Temporal development of the infant oral microbiome. (2nd November 2022) - Blum, Jordan; Silva, Mihiri; Byrne, Samantha J.; Butler, Catherine A.; Adams, Geoffrey G.; Reynolds, Eric C.; Dashper, Stuart G.
Abstract: The human oral microbiome is becoming recognized as playing roles in health and disease well beyond the oral cavity over the lifetime of the individual. The oral microbiome is hypothesized to result from specific colonization events followed by a reproducible and ordered development of complex bacterial communities. Colonization events, proliferation, succession and subsequent community development are dependent on a range of host and environmental factors, most notably the neonate diet. It is now becoming apparent that early childhood and prenatal influences can have long term effects on the development of human oral microbiomes. In this review, the temporal development of the infant human oral microbiome is examined, with the effects of prenatal and postnatal influences and the roles of specific bacteria. Dietary and environmental factors, especially breastfeeding, have a significant influence on the development of the infant oral microbiome. The evidence available regarding the roles and functions of early colonizing bacteria is still limited, and gaps in knowledge where further research is needed to elucidate these specific roles in relation to health and disease still exist.